Implementation of Safety Stock and ROP Methods in the Inventory Information System of Kava Kudus Coffee Shop - Taufiq, Muhammad Bagas; Setiawan, R Rhoedy; Irawan, Yudie (Sistemasi: Jurnal Sistem Informasi, 2025)
Manual stock management, particularly through paper based record keeping, remains a challenge for culinary businesses such as Kava Coffee Shop in Kudus. Issues such as inaccurate records, delayed reordering, and the absence of notifications for expired or damaged ingredients can lead to stockouts or overstocking. This study aims to design a web-based inventory information system incorporating the Safety Stock and Reorder Point (ROP) methods to optimize the management of perishable raw materials. The system was developed using the Waterfall model, covering requirements analysis, design with Use Case and Activity Diagrams, feature implementation, and testing through the Black-box method. Key system features include minimum stock notifications, expiration tracking, transaction management, and damaged goods returns. Testing results show that the system performs according to specifications, achieving a 100% success rate across functional scenarios. Compared to previous studies, this system demonstrates superiority by being web-based, focusing on perishable goods, and offering integrated features. Therefore, the system can enhance record accuracy, accelerate decision-making, and ensure the availability and quality of raw materials at Kava Coffee Shop.